Improving Student Reading Comprehension Using Narrative Text Question and Answer Method - Hanny Kusuma Wardani; Aswir Aswir (Jurnal Studi Guru dan Pembelajaran, 2022)
This research aimed to improve students reading comprehension by using narrative text question and answer method. The method that use in this study was question and answer discussion between students and teacher. The application of the study used mixed method research with pre-test, post-test and discussion. The teacher asked students to read a narrative text about Bawang Merah dan Bawang Putih. The research was conducted at SMA Bakti Idhata, located in Jakarta, consist of 40 students in the 10th grade class of X-A. The students’ classification score divided into seven categories, starting from the highest and the lowest: excellent, very good, good, fairly good, fair, poor, and very poor. The students who got the score (excellent: 86-95) was 12 students, but there was no students who got it before. Most of the students got (good: 76-85) which was 20 students, while before that, 16 students got these score. The student who got (fairly good: 66-75) was 7 students, while before it was 16 students which means there was significant different after it conducted the treatment. The students who got (fair: 56-65) before the treatment was 5 students, but now it was nobody. And last, the students who got (poor: 36-55) was only 1 students, while before that, it has 3 students. The value of students who have been taught using question and answer method was higher than the value of students who were not taught using question and answer method. This conclude that using question and answer method were effective in improving students reading comprehension